PENGARUH IKLIM ORGANISASI TERHADAP PRESTASI KERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN HALMAHERA TENGAH - UMASANGADJI, FATMAWATI; LENGKONG, FLORENCE DAICY; OGOTAN, MARTHA (Sam Ratulangi University, 2014)
This researchmoved from themain problems, namely: the extent to which organizationalclimate on the performanceof employeesat the District Secretariatof Central Halmahera. Thus, thisresearchaims: toanalyze the influence oforganizational climateon the performanceof employeesat the DistrictSecretariatof Central Halmahera.This study uses aquantitative approach to the application of descriptive and explanatory. Andinformation collected through questionnaires distributed to the technique 72 respondents, and is equippedwith observation and documentation techniques, and then analyzed by applying a frequency table analysistechnique, the product moment correlation and simple linear regression.Based on the analysisof data, it is known that: the results of a descriptive analysis of the technique ofanalysis tables (frequency tables) it is known that the distribution of respondents' answers to theOrganizational Climate variables are in the category of